DR-70 as a novel diagnostic biomarker for gastric cancer - Arhan, Mehmet; Yılmaz, Hülya; Önal, İbrahim K.; Kocabıyık, Murat; Erdal, Harun; İbiş, Mehmet (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To assess the utility of the DR-70 immunoassay in the diagnosis of gastric cancer. Materials and Methods: A total of 29 patients with histologically proven malignant gastric tumor and 29 healthy blood donors were enrolled in this study. DR-70 immunoassay was performed using an enzyme-linked immunosorbent assay kit to quantify the serum levels of fibrin degradation products. Results: The DR-70 values in patients with gastric cancer significantly differed from the values in controls (p<0.0001). Receiver operating characteristic curve analysis revealed ≥1.45 µg/mL as the best cut-off value to distinguish between patients with gastric cancer and healthy controls. The area under the receiver operating characteristic curve was 0.871. Using ≥1.45 µg/mL as the cut-off value, the DR-70 immunoassay showed a good clinical performance with a sensitivity of 82.8% and a specificity of 79.3%. The positive predictive value was 80.0%, and the negative predictive value was 82.1%. Conclusion: The DR-70 immunoassay reliably differs between gastric cancer and healthy controls, promising to become a useful cancer detection tool in clinical practice.